2016
DOI: 10.1111/age.12515
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic β‐carotene oxygenase 2 knockout results in yellow fat in sheep via CRISPR/Cas9

Abstract: The recently emerged CRISPR/Cas9 approach represents an efficient and versatile genome editing tool for producing genetically modified animals. Β-carotene oxygenase 2 (BCO2) is a key enzyme in the progress of β-carotene metabolism and is associated with yellow adipose tissue color in sheep. We have recently demonstrated targeted multiplex mutagenesis in sheep and have generated a group of BCO2-disrupted sheep by zygote injection of the CRISPR/Cas9 components. Here, we show that biallelic modification of BCO2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…When SCNT is mastered by the laboratory, the low efficient rate will be compensated with most of the healthy born animals carrying the desired mutation. Genome editing mediated by SCNT is applied by some laboratories in some kind of projects (e.g., multiplex editing), but the high efficiency of CRISPR after direct microinjection into zygotes has allowed an easier approach (sheep: [6,7,15,16]; goats: [9,17]; pigs: [11,13]). All together, these reports showed that with CRISPR it is possible to perform direct microinjection into the zygote of different species, with minimum effects on developmental competence and pregnancy rates, high newborn survival rate, and high editing rate with acceptable homozygous proportion.…”
Section: Embryo Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…When SCNT is mastered by the laboratory, the low efficient rate will be compensated with most of the healthy born animals carrying the desired mutation. Genome editing mediated by SCNT is applied by some laboratories in some kind of projects (e.g., multiplex editing), but the high efficiency of CRISPR after direct microinjection into zygotes has allowed an easier approach (sheep: [6,7,15,16]; goats: [9,17]; pigs: [11,13]). All together, these reports showed that with CRISPR it is possible to perform direct microinjection into the zygote of different species, with minimum effects on developmental competence and pregnancy rates, high newborn survival rate, and high editing rate with acceptable homozygous proportion.…”
Section: Embryo Manipulationmentioning
confidence: 99%
“…These often disrupt open reading frames, effectively creating gene knockouts. This mechanism led to the generation of the first successful disruption of endogenous genes by CRISPR-Cas system in livestock (sheep [6,7], goats [8,9], cows [10] and pigs [11e14]). On the other hand, the HDR pathway employs a homologous repair template to fix the DSB.…”
Section: Introductionmentioning
confidence: 99%
“…Seven ASE SNPs were identified in BCO2 gene from the samples of subcutaneous fat and tail fat, six of these ASE SNPs were located in exon region of the gene and the remaining one ASE SNP was located in its 3'-UTR region. Knocking out the biallelic BCO2 gene could lead to yellow fat in Tan sheep and a nonsense mutation in this gene is strongly related to the yellow fat phenotype in Norwegian sheep [76,77]. A total of seven ASE SNPs were found in PM20D1 gene, which involved in the cellular lipid process.…”
Section: Discussionmentioning
confidence: 99%
“…Another transgenic pig exhibited an increased content of Omega‐3 fatty acids in meat due to the expression of the fatty acid desaturase fat‐1 from Caenorhadbitis elegans (Lai et al., ). Using CRISPR, an increase in yellow fat in sheep meat has been recently achieved by removing beta‐carotene oxygenase 2 (BCO2) (Niu et al., ).…”
Section: Improved Animal Productsmentioning
confidence: 99%